Comparison of clinical outcomes following delivery of budesonide by both vibrating mesh nebulizer and jet nebulizer in premature infants with bronchopulmonary dysplasia - Zhou, Jian-Fu; Zhang, Yi-Bing; Zhang, Zhi-Wei (Frontiers in Pediatrics, 2023)
Background: This study aimed to compare the efficacy of budesonide inhalation suspension administered via a vibrating mesh nebulizer versus a jet nebulizer in the treatment of premature infants with bronchopulmonary dysplasia (BPD) undergoing high-frequency oscillatory ventilation (HFOV). Methods: Between July 2020 and July 2022, we retrospectively analyzed the medical records of 36 preterm infants diagnosed with BPD who underwent HFOV. Based on the nebulizer type used, infants were categorized into the vibrating mesh nebulizer group (VMN group) or the jet nebulizer group (JN group). Post-nebulization outcomes, such as the duration of mechanical ventilation, length of stay in the neonatal intensive care unit (NICU), ventilator-associated parameters, and arterial blood gas metrics, were compared between the two groups. Treatment-associated complications were also documented.Results: No significant differences were noted between the VMN and JN groups in terms of mechanical ventilation duration (p=0.519), NICU length of stay (p=0.112), ventilator-associated parameters, or complications (p=0.700). However, after 2 weeks of treatment, the oxygenation index (p=0.012) and arterial partial pressure of carbon dioxide (p=0.006) were more favorable in the VMN group compared to the JN group.Among premature infants with BPD on HFOV, for administration of budesonide inhalation suspension resulted in an improved oxygenation index and reduced arterial partial pressure of carbon dioxide when compared to a jet nebulizer, indicating superior therapeutic efficacy.